Monitoring of Ionospheric Variability Using the Low lAtitude Long Range Ionospheric raDar (LARID): Capabilities, Advantages and Limitations - Wenjie Sun; Guozhu Li; Baiqi Ning; Lianhuan Hu; Yuichi Otsuka; Guofeng Dai; Haiyong Xie; Xiukuan Zhao; Yi Li; Atsuki Shinbori; Michi Nishioka; Septi Perwitasari; et al. (Space Weather)
Abstract A Low lAtitude long Range Ionospheric raDar (LARID), which was built recently at Dongfang (19.2°N, 108.8°E, magnetic latitude 13.9°), Hainan Is., China, is employed to study the ionospheric variability over a large region. The LARID consists of two high frequency (HF) coherent backscatter radars, looking toward east and west, respectively, with a field‐of‐view covering a wide longitude from Africa to Pacific. Here we report some results by the LARID, with main focus on its capabilities, advantages and limitations in monitoring ionospheric variability. The results show that the LARID can detect various ionospheric variations at low latitudes, including (a) sequentially generated equatorial plasma bubbles over a longitude span of ∼80°, (b) near‐range E region irregularities drifting across more than 1,000 km, (c) ionospheric background information retrieved from ground scatters, (d) traveling ionospheric disturbances, and (e) sporadic E structures reflecting HF radio waves at low elevation angles. It is demonstrated that the LARID provides an important tool for investigating different types of ionospheric variability over a broad region, especially over the Indian Ocean and west Pacific, and will contribute significantly to the regional ionospheric weather forecasting.